Repurchase intention towards Huawei smartphone brand - Wong, Jin Ee (2019)
In this research, the aim is to focus on the consumer repurchase intention toward Huawei smartphone brand. There has been previous research that consumer have some pre-set anticipation with a particular brand and would purchase the product to satisfied their desire. Consumer satisfaction depends on several on several ways that the firm serve its consumers to fulfil their needs by providing goods and services effectively and effectively. Researcher has identified the consumer to have the intention to repurchase that are affected by various factors such as peer influence, price, quality, brand image and brand loyalty. Researcher will explain about the dependent variable and each independent variable in literature review. Besides, the hypothesis also showed there is a significant positive relationship from price, quality, brand image, peer influence and brand loyalty towards consumer repurchase intention towards Huawei smartphone brand based on the research of previous researchers. The primary data were collected through google form and secondary data is based on the journal and website. The sample size for this research is 300 respondents and Huawei user will be the target population. Next, research instrument and constructs management will be conducted. Besides that, data processing and data analysis will be carried out as well. After collecting the data from survey questionnaire, the researcher will analysed through Statistical Package for Social Science (SPSS) version 20.0. Research will interpret the result with charts and table. Lastly, managerial implication, limitations and recommendations for prospect research was included in the study. This research will also contribute to academics who wish to conduct study in related field to gain deeper insights and marketer to understand the needs and wants of consumers.